Sociology in our times : the essentials - Kendall, Diana Elizabeth (Wadswoth Cengage Learning, 2010)
Focuses on diversity and inequality, emphasizing social consciousness and active participation in bettering the world around us. This title includes a Sociology Works! feature; assignable Reflect & Analyze questions that conclude selected features; photo essays, with assignable video activities; and concept review tables